2017
DOI: 10.1186/s12880-016-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Newly recognized cerebral infarctions on postmortem imaging: a report of three cases with systemic infectious disease

Abstract: BackgroundPostmortem imaging (PMI) refers to the imaging of cadavers by computed tomography (CT) and/or magnetic resonance imaging (MRI). Three cases of cerebral infarctions that were not found during life but were newly recognized on PMI and were associated with severe systemic infections are presented.Case presentationsAn 81-year-old woman with a pacemaker and slightly impaired liver function presented with fever. Imaging suggested interstitial pneumonia and an iliopsoas abscess, and blood tests showed liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…In autopsy series study of NBTE by Llenas-García et al 5 tuberculosis was associated in 3 cases (13.6% of total), of which one case also had systemic lupus erythematosus. In the post-mortem imaging study by Noriki et at, 6 one case with military tuberculosis also showed NBTE involving the aortic valve as a cause for emboli causing cerebral infarction. Though the precise pathogenetic association between tuberculosis and NBTE is not clear, endothelial damage and exposure of the subendothelial collagen to platelets as a result of septicemia may be the basic mechanism for the formation of thrombi over leaflets.…”
Section: Discussionmentioning
confidence: 92%
“…In autopsy series study of NBTE by Llenas-García et al 5 tuberculosis was associated in 3 cases (13.6% of total), of which one case also had systemic lupus erythematosus. In the post-mortem imaging study by Noriki et at, 6 one case with military tuberculosis also showed NBTE involving the aortic valve as a cause for emboli causing cerebral infarction. Though the precise pathogenetic association between tuberculosis and NBTE is not clear, endothelial damage and exposure of the subendothelial collagen to platelets as a result of septicemia may be the basic mechanism for the formation of thrombi over leaflets.…”
Section: Discussionmentioning
confidence: 92%
“…The PMI was performed at the Ai center at the University of Fukui, 3 months before dissection, using an 8‐slice multi‐detector CT scanner (Hitachi Medico, Tokyo, Japan) used exclusively for autopsies, as described previously . The corpus was placed in the supine position, and a full‐body scan from the vertex to the toes was performed.…”
Section: Treatment Of the Corpusmentioning
confidence: 99%
“…First, two radiologists (KK and TS) read the postmortem images of the corpus without any medical information and deduced the immediate cause of death. The algorithm for diagnosis is described in a previous article . Then, the anatomy instructor (SI) revealed the medical information.…”
Section: Treatment Of the Corpusmentioning
confidence: 99%
See 2 more Smart Citations